Titanium Application Increases Phosphorus Uptake Through Changes in Auxin Content and Root Architecture in Soybean (Glycine Max L.) - Hussain, Sajad; Shafiq, Iram; Skalicky, Milan; Brestic, Marian; Rastogi, Anshu; Mumtaz, Maryam; Hussain, Muzammil; Iqbal, Nasir; Raza, Muhammad Ali; Manzoor, Sumaira; Liu, Weiguo; Yang, Wenyu (Frontiers in Plant Science, 2021)
Phosphorus deficiency or low rate of phosphorus uptake is considered as one of the main limiting factors for crop growth. Titanium (Ti) application increases the nutrient uptake by affecting the root growth; however, the role of Ti in plant biology, specifically its application under low light and phosphorus stress, has never been reported. Therefore, a pot experiment was conducted to investigate the effect of Ti on phosphorus uptake under low P and shade stress. Different concentrations of Ti (T1 = 0 mgL-1, T2 = 125 mgL-1, T3 = 250 mgL-1, T4 = 500 mgL-1 and T5 = 1000 mgL-1) were foliar applied on soybean seedlings grown in high phosphorus (HP = 100 mgkg-1) and low phosphorus (LP = 10 mgkg-1) concentrations in the pots under normal light (NL) and shade (SC) conditions. The results indicated that under co-occurring SC and LP stress, Ti significantly improved root length and root surface area, decreased rhizosphere soil pH, boosted antioxidant enzymatic activities and enhanced the photosynthetic efficiency of soybean plants grown under combined SC and low P stress. Furthermore, under SC, the effect of Ti on plants grown in LP was more obvious as compared to those grown in HP. Ti treatment T3 significantly increased shoot and root dry matter under SC and LP. Under SC with LP, the Ti treatment (T3) increased the (photosynthetic) Pn rate by 44.78%. In LP, quantum yield of PSII photochemistry (Fv/Fm) values did not change significantly in response to Ti treatments as compared to T0 except for T3 which resulted in a significant increase (15.12%) against control. In conclusion our findings confirms that foliar application of Ti compensates the LP and SC stress induced inhibited growth by improving root architectural traits, rhizosphere soil environment (pH), root Auxin content, photosynthetic capacity, antioxidants activity and phosphorus uptake in soybean.